Synthesis of Polycyclic Natural Products through Skeletal Rearrangement - Yokoshima, Satoshi (Synlett, 2020)
Construction of rings through reliable reactions followed by changes in the ring size or the connectivity through skeletal rearrangement provides molecules with a wide range of skeletons. In this account, our syntheses of polycyclic natural products through skeletal rearrangement are discussed.1 Introduction2 Synthesis through Changes in the Ring Size3 Synthesis by Biomimetic Strategies4 Synthesis through Metathesis5 Synthesis through Temporary Formation of a Ring6 Conclusion
Keywords: alkaloids; cycloaddition; natural products; rearrangement; total synthesis